Let's Talk About Infertility!: Interactive Storytelling As Immersive Medium For Educational Content - Lalitya Talitha Pinasthika (ULTIMART Jurnal Komunikasi Visual, 2022)
Infertility is a problem for some couples of childbearing age in Indonesia. This problem affects one-third of married couples, yet the discussion regarding infertility has not been thoroughly heard. This research focuses on introducing infertility to the general public, intending to transform the general perspective, so the problems that occur in the couple's household will not be disrupted with misinformed myths surrounding infertility. The idea is to deliver information through an interactive story that involves the user in choosing the storyline. The research methodology used combines qualitative methods through observations on infertility online forums and Focus Group Discussions. The quantitative methodology was carried out in two stages, before testing the prototype to obtain public perceptions of infertility, then again after the prototype test to measure users’ immersion using a Likert scale. The study revealed that conveying problems through a story that requires user involvement in selecting storylines affects readers' immersion in digesting educational reading content. Keywords: interactive; storytelling; infertility; immersive